Primary B Cell Lymphoma of the CNS Mimicking Anti-LGI1 Limbic Encephalitis - Thomas, Christian; Lehrich, Christoph; Gross, Catharina C.; Wiendl, Heinz; Meuth, Sven G.; Melzer, Nico (Frontiers in Neurology, 2018)
Limbic encephalitis is a potentially paraneoplastic type of encephalitis mainly involving the limbic system. Recently, diagnostic criteria comprising clinical presentation as well as imaging, laboratory and electrophysiological findings have been established. Here, we show that incipient primary central nervous system lymphoma can almost perfectly mimic limbic encephalitis including positive testing for anti-LGI1 antibodies illustrating the need for thorough interpretation of initial laboratory and radiologic findings and tight follow-up examinations.